Mapping The Development of Japanese Studies Journals In Indonesia - Anwar, Fithyani (NAWA: Journal of Japanese Studies, 2025)
The Japanese studies field has significantly expanded globally, encompassing diverse themes from traditional cultural aspects to contemporary issues such as globalization and international relations. In Indonesia, Japanese studies play a pivotal role in fostering academic and cultural ties with Japan. The growth of this field is evidenced by the increasing number of academic programs and publications focusing on Japanese language, literature, and culture. Currently, Indonesia hosts 27 Japanese studies journals, which serve as key platforms for disseminating research and strengthening academic engagement. This study adopts a qualitative descriptive approach to map and analyze the development of these journals. It identifies key challenges such as meeting national accreditation standards set by SINTA, ensuring consistent publication quality, and addressing operational sustainability. Other notable issues include article processing charges (APCs) and the need for alignment with international publication norms. Despite these challenges, integrating Japanese cultural philosophy into journal names and designs demonstrates a strong commitment to the field’s identity. In addition, mandatory publication requirements for faculty members and collaborations with academic associations such as ASJI, ASPBJI, and KPSJI provide critical opportunities for these journals to develop further. Rather than merely offering a general overview, this study presents specific insights into the conditions and trajectories of Japanese studies journals in Indonesia, shedding light on their role in strengthening Indonesia’s contribution to global Japanese studies scholarship.